Validation of Normal Human Bronchial Epithelial Cells as a Model for Influenza A Infections in Human Distal Trachea. (May 2015) - Davis, A. Sally; Chertow, Daniel S.; Moyer, Jenna E.; Suzich, Jon; Sandouk, Aline; Dorward, David W.; Logun, Carolea; Shelhamer, James H.; Taubenberger, Jeffery K.
Primary normal human bronchial/tracheal epithelial (NHBE) cells, derived from the distal-most aspect of the trachea at the bifurcation, have been used for a number of studies in respiratory disease research. Differences between the source tissue and the differentiated primary cells may impact infection studies based on this model. Therefore, we examined how well-differentiated NHBE cells compared with their source tissue, the human distal trachea, as well as the ramifications of these differences on influenza A viral pathogenesis research using this model. We employed a histological analysis including morphological measurements, electron microscopy, multi-label immunofluorescence confocal microscopy, lectin histochemistry, and microarray expression analysis to compare differentiated NHBEs to human distal tracheal epithelium. Pseudostratified epithelial height, cell type variety and distribution varied significantly. Electron microscopy confirmed differences in cellular attachment and paracellular junctions. Influenza receptor lectin histochemistry revealed that α2, 3 sialic acids were rarely present on the apical aspect of the differentiated NHBE cells, but were present in low numbers in the distal trachea. We bound fluorochrome bioconjugated virus to respiratory tissue and NHBE cells and infected NHBE cells with human influenza A viruses. Both indicated that the pattern of infection progression in these cells correlated with autopsy studies of fatal cases from the 2009 pandemic.